The Influence of Entrepreneurship Knowledge on Entrepreneurial Interest in Medan Market Center with Self Efficacy as an intervening Variable - Wenikha Waldyatri; Bunga Aditi; Sopi Pentana (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2021)
The author's purpose of conducting research is to determine the effect of Knowledge of Entrepreneurship on Interest in Entrepreneurship, to determine the effect of Self Efficacy on Interest in Entrepreneurship, to determine the effect of Knowledge of Entrepreneurship on Self Efficacy, to determine the effect of Knowledge of Entrepreneurship on Interest in Entrepreneurship with Self Efficacy as a Moderating Variable at the Medan Market Center . The sample in this study is 100 people who are entrepreneurs in the Medan Market Center. This research was collected through a questionnaire which was processed and analyzed using Path Analysis. Then test the quality of the data used is the validity test using Significant and reliability test using Cronbach Alpha. To test the hypothesis in this study. Researchers used the t test, and F test and did a determination test. The results of this study indicate that there is a positive influence of entrepreneurial knowledge on interest in entrepreneurship, there is a positive influence of self-efficacy on interest in entrepreneurship, there is a positive influence of entrepreneurial knowledge on self-efficacy and there is an indirect effect of entrepreneurial knowledge on interest in entrepreneurship through self-efficacy. Thus the interest in entrepreneurship becomes an integral part of entrepreneurial knowledge as an intermediary, so that entrepreneurial knowledge can indirectly affect self-efficacy.